2021
DOI: 10.1016/j.xhgg.2020.100015
|View full text |Cite
|
Sign up to set email alerts
|

Missense substitutions at a conserved 14-3-3 binding site in HDAC4 cause a novel intellectual disability syndrome

Abstract: Summary Histone deacetylases play crucial roles in the regulation of chromatin structure and gene expression in the eukaryotic cell, and disruption of their activity causes a wide range of developmental disorders in humans. Loss-of-function alleles of HDAC4 , a founding member of the class IIa deacetylases, have been reported in brachydactyly-mental retardation syndrome (BDMR). However, while disruption of HDAC4 activity and deregulation of its downstream targets may contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Following these observations, we explored whether the effect of extinction learning on HDAC3, HDAC4, and CBP occupancy at the Nr4a2 gene promoter is due, in part, to a role of ADRAM as a scaffold for 14-3-3. Previous work has shown that the phosphorylation-dependent binding of 14-3-3 to HDAC4 serves to regulate its nuclear activity by sequestering HDAC4 from the nucleus into the cytoplasm in a signal-dependent manner ( McKinsey et al, 2000 ; Wakeling et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following these observations, we explored whether the effect of extinction learning on HDAC3, HDAC4, and CBP occupancy at the Nr4a2 gene promoter is due, in part, to a role of ADRAM as a scaffold for 14-3-3. Previous work has shown that the phosphorylation-dependent binding of 14-3-3 to HDAC4 serves to regulate its nuclear activity by sequestering HDAC4 from the nucleus into the cytoplasm in a signal-dependent manner ( McKinsey et al, 2000 ; Wakeling et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, the variant might not have appeared convincing to the evaluators leading to it not being scored. However, certain missense variants in HDAC4 were recently described to cause a syndromic NDD entity and a gain‐of‐function effect was discussed based on nucleocytoplasmic mislocation of the protein (Wakeling et al, 2021). The variant in TrioReal_66 affects a different protein region, which is however highly conserved and represents a structured alpha helix in the AlphaFold protein model of HDAC4.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that haploinsufficiency of HDAC4 for BDE is not completely penetrant ( Villavicencio-Lorini et al, 2013 ) and is not sufficient to cause intellectual disability ( Wheeler et al, 2014 ). More recently, heterozygous de novo missense variants affecting amino acid residues involved in phosphorylation-dependent binding of 14-3-3 proteins (see below) and control of the nucleocytoplasmic shuttle, have been identified in individuals with delayed developmental milestones, intellectual disability and hypotonia, a phenotype distinct from 2q37 deletion syndrome ( Wakeling et al, 2021 ). Although HDAC5 is the predominant family member in the central nervous system ( Brancolini et al, 2021 ), the role of HDAC4 in controlling synaptic gene expression and the alterations in neurotransmission, learning, and memory observed in some but not all mouse models with dysregulated HDAC4 support a possible role in central nervous system (CNS) functions ( Wu et al, 2016 ).…”
Section: The Hdac4 Genementioning
confidence: 99%